2017
DOI: 10.1002/term.2330
|View full text |Cite
|
Sign up to set email alerts
|

Human umbilical cord derivatives regenerate intervertebral disc

Abstract: Intervertebral disc (IVD) degeneration is characterized by the loss of nucleus pulposus (NP), which is a common cause for lower back pain. Although, currently, there is no cure for the degenerative disc disease, stem cell therapy is increasingly being considered for its treatment. In this study, we investigated the feasibility and efficacy of human umbilical cord mesenchymal stem cells (MSCs) and chondroprogenitor cells (CPCs) derived from those cells to regenerate damaged IVD in a rabbit model. Transplanted c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 48 publications
1
37
0
Order By: Relevance
“…Stem cell‐based therapies can greatly impact the field of regenerative medicine. MSCs have been used in preclinical and clinical studies to treat degenerative diseases, such as AD (Cui et al, ; Han et al, ; J. Shin et al, ; X. Wang, Ma, et al, ), DDD (Ahn et al, ; Beeravolu et al, ; Pereira et al, ; Perez‐Cruet et al, ), MS (Harris et al, ; Nasri et al, ; Planchon et al, ), PD (Jamali et al, ; H. Kim, Lee, et al, ), and RDD (Mead, Amaral, & Tomarev, ), as summarized in Table . The regenerative mechanisms of transplanted MSCs for these diseases are still unclear; however, some reports have suggested that MSCs have the potential to differentiate or have paracrine effects in vivo (Lee, Choi, Cha, & Hwang, ).…”
Section: Promising Applications Of Mscsmentioning
confidence: 99%
See 4 more Smart Citations
“…Stem cell‐based therapies can greatly impact the field of regenerative medicine. MSCs have been used in preclinical and clinical studies to treat degenerative diseases, such as AD (Cui et al, ; Han et al, ; J. Shin et al, ; X. Wang, Ma, et al, ), DDD (Ahn et al, ; Beeravolu et al, ; Pereira et al, ; Perez‐Cruet et al, ), MS (Harris et al, ; Nasri et al, ; Planchon et al, ), PD (Jamali et al, ; H. Kim, Lee, et al, ), and RDD (Mead, Amaral, & Tomarev, ), as summarized in Table . The regenerative mechanisms of transplanted MSCs for these diseases are still unclear; however, some reports have suggested that MSCs have the potential to differentiate or have paracrine effects in vivo (Lee, Choi, Cha, & Hwang, ).…”
Section: Promising Applications Of Mscsmentioning
confidence: 99%
“…The regenerative mechanisms of transplanted MSCs for these diseases are still unclear; however, some reports have suggested that MSCs have the potential to differentiate or have paracrine effects in vivo (Lee, Choi, Cha, & Hwang, ). Our recent preclinical studies showed that nucleus pulposus‐like cells (NPCs) derived from MSCs were more efficacious than MSCs in a rabbit model of DDD (Beeravolu et al, ; Perez‐Cruet et al, ). The transplanted MSC‐derived NPCs survived, migrated, and integrated in the nucleus pulposus (NP) of the intervertebral discs (IVDs).…”
Section: Promising Applications Of Mscsmentioning
confidence: 99%
See 3 more Smart Citations